Frequency of tooth brushing and associated factors among adolescents in western Norway - Arild Vaktskjold (Norsk Forening for Epidemiologi, 2019)
Dental caries is the most prevalent disease in Norway and worldwide, and daily tooth brushing with fluoridated toothpaste is the main preventative measure when diets contain sugary foods. Tooth brushing is an important public health indicator, as the frequency of brushing also has been positively associated with good health in general. In Norway, brushing twice a day is the official recommendation. Our aim was to assess the frequency of tooth brushing among pupils in secondary school in two counties in western Norway, and to identify factors associated with brushing more than once a day. All 59 borough administrations in the two counties were invited to participate in the Ungdata survey in 2015-16; 26 agreed. In total 8,725 pupils filled in the electronic questionnaire (82%). Some 69% brushed their teeth more frequently than once a day, specifically 76% of whom were girls and 63% were boys (adjusted odds ratio=2.0). Of the boys, 6.5% did not brush daily. In 8-10th school grade 71% brushed more than once a day, compared to 65% in 11-13th grade. Out of 28 a priori selected factors, eight were independently associated with frequency of tooth brushing. Besides gender, the strongest associations observed were for frequency of brisk physical exercise, parents being informed about their adolescent's whereabouts, and satisfaction with one's own health.